Likely uptakers of the COVID-19 vaccinations in Cross River South Senatorial District, Nigeria - Undelikwo, Veronica Akwenabuaye; Bassey, Glory Eteng; Bassey, Nkoyo Patrick; Ubi, Lilian Otu; Egong, Mathew Mike (Intelektual Pustaka Media Utama, 2025)
The COVID-19 outbreak resulted in widespread concern and disruption globally. The development of vaccines was a significant focus in mitigating the impact of the deadly virus. However, vaccine uptake in many regions has been challenging, including the Cross River South Senatorial District. This study examines the socio-demographic variables influencing the adoption of the COVID-19 vaccine. Data was collected from 750 respondents through the questionnaire. Bivariate analysis using Chi-square statistics was used to evaluate the association between COVID-19 vaccination and covariates, including age, sex, location, occupation status, religion, educational status, and availability of COVID-19 vaccination sites. A logistic regression model was used to ascertain this connection. Based on the findings, COVID-19 uptake was 32.3%. Employment status was the only variable statistically significant with the uptake of the COVID-19 vaccine. When promoting the use of vaccines, consideration should be given to variables other than personal characteristics. With the low uptake of the COVID-19 vaccines, continued efforts are needed to improve the vaccination uptake rate by all segments of the study population.